PRIMARY ADRENAL LYMPHOMA AS AN AETIOLOGY OF FLUCTUATING BILATERAL ADRENAL MASSES - Azman, SS Wan; Nasruddin, AB; Sidhu, J; Pang, Philip BC; Awang, A (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Primary adrenal lymphoma (PAL) is rare, with fewer than 200 reported cases. They usually present with bilateral adrenal masses affecting elderly males, with diffuse large B cell lymphoma as the most common subtype (78%). RESULTS We describe the case of a 60-year-old woman with severe right flank pain for three days. She denied any constitutional and B symptoms, and any tuberculosis contacts. There were no headaches, palpitations or hypertensive episodes. Ultrasound followed by computed tomography (CT) of the abdomen demonstrated a large right suprarenal (8 cm x 5.7 cm x 7.3 cm) and a small enhancing left adrenal mass (1.1 cm x 1.3 cm x 2.3 cm). Urine metanephrines, aldosterone:renin ratio, dehydroepiandrosterone and overnight dexamethasone suppression test were normal. A repeat CT three months later showed size reduction in the right suprarenal (3.4 cm x 3.2 cm x 3.4 cm) and increase in the left suprarenal mass (2.9 cm x 3.7 cm x 3.8 cm). Both were heterogeneously enhanced (39 and 36 HU, absolute contrast washout 39% and 31%, respectively). One month later, there was further decline in size of the right suprarenal (2.2 cm x 2.3 cm x 2.5 cm) and completely resolved left suprarenal mass on abdominal sonography. She denied taking any steroid-containing medication. Two months afterward, she presented with symptom recurrence. Repeat CT adrenal protocol showed large masses arising from both adrenal glands (8.5 cm x 5.9 cm x 7.6 cm and 5.0 cm x 3.2 cm x 3.8 cm, respectively). Endoscopic ultrasoundguided fine needle biopsy of the left adrenal revealed highgrade diffuse large B-cell lymphoma. She was referred to haematology for chemotherapy. CONCLUSION PAL must be considered as one of the differentials of bilateral adrenal masses. Size fluctuation and rapid progression were not associated with any systemic symptoms